Maternal Pre-Pregnancy Obesity Combined With Abnormal Glucose Metabolism Further Increases Adverse Pregnancy Outcomes in Chinese Pregnant Women - Li, Mei-Fang; Ke, Jiang-Feng; Ma, Li; Wang, Jun-Wei; Zhang, Zhi-Hui; Li, Jing-Bo; Li, Lian-Xi (Frontiers in Endocrinology, 2022)
Aims: Our aim was to evaluate the separate and combined effects of maternal pre-pregnancy obesity and gestational abnormal glucose metabolism (GAGM) on adverse perinatal outcomes. Methods: 2796 Chinese pregnant women with singleton delivery were studied, including 257 women with pre-pregnancy obesity alone, 604 with GAGM alone, 190 with both two conditions and 1745 with neither pre-pregnancy obesity nor GAGM as control group. The prevalence and risks of adverse pregnancy outcomes were compared among the four groups. Results: Compared with the normal group, pregnant women with maternal pre-pregnancy obesity alone, GAGM alone and both two conditions faced significantly increased risks of pregnancy-induced hypertension (PIH) (odds ratio (OR) 4.045, [95% confidence interval (CI) 2.286-7.156]; 1.993 [1.171-3.393]; 8.495 [4.982-14.485]), preeclampsia (2.649 [1.224-5.735]; 2.129 [1.128-4.017]; 4.643 [2.217-9.727]), cesarean delivery (1.589 [1.212-2.083]; 1.328 [1.095-1.611]; 2.627 [1.908-3.617]), preterm delivery (1.899 [1.205-2.993]; 1.358 [0.937-1.968]; 2.301 [1.423-3.720]), macrosomia (2.449 [1.517-3.954]; 1.966 [1.356-2.851]; 4.576 [2.895-7.233]), as well as total adverse maternal outcomes (1.762 [1.331-2.332]; 1.365 [1.122-1.659]; 3.228 [2.272-4.587]) and neonatal outcomes (1.951 [1.361-2.798]; 1.547 [1.170-2.046]; 3.557 [2.471-5.122]). Most importantly, there were no obvious risk differences in adverse pregnancy outcomes between maternal pre-pregnancy obesity and GAGM group except PIH, but pregnant women with both obesity and GAGM exhibited dramatically higher risks of adverse pregnancy outcomes than those with each condition alone. Conclusions: Maternal pre-pregnancy obesity and GAGM were independently associated with increased risks of adverse pregnancy outcomes. The combination of pre-pregnancy obesity and GAGM further worsens adverse pregnancy outcomes compared with each condition alone.